ADSORPTION OF BENZENE WITH CYCLOHEXANE AND N-ALKANES SILICA GEL - F. Lama, Ricardo (2004)
This work embodies the results of an evaluation of liquid phase adsorption data reported in literature of binary mixtures of benzene with cyclohexane, benzene with n-alkanes in sílica gel and values obtained in this investigation in the benzene-cyclohexane-sílica gel system with the purpose of determining the surface areas of the adsorbents The surface areas per gram of adsorbent, determined from liquid adsorption data of solutions of benzene with cyclohexane are 22 per cent smaller than those obtained from nitrogen gas adsorption and 9 per cent greater in the case of solutions of benzene with n-alkanes.